PENGELOLAAN POPULASI KETAM KELAPA (Birgus latro) DI KAWASAN TAMAN WISATA ALAM PULAU MARSEGU, KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - , Andre Tuhumury ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Coconut crab (Birgus latro) is a wild animal that has important economics value because of itâs potential as an export commodity. Coconut crab was inhabitated coastal ecosystems and currently under threat. These crabs protected by the SK Menhut No. 12/Kpts-II/Um/1987. In general, a good conservation plan for endangered species will aim to preserve optimal number and living in a good habitat quality. This study aimed to estimates the population size and habitat characteristics of the coconut crabs, to understand the public perception around the nature recreational park, analyze the population management program and to develop strategies and plans for management of coconut crabs in the TWA Marsegu Island, District of West Seram, Maluku Province. The results showed that coconut crab population size was 117 individual. 131 individual on the upper class limit and 105 individual in the lower class limit. Analysis of the relationship between habitat and population of crabs showed that ground cover plants (X2), pole density (X4), and the number of coconut trees (X6) have a significant impact. Society expressed strong support for high-resource management efforts coconut crab in the TWA Marsegu Island. Priority of strategies adopted in the management of populations of coconut crabs (Birgus latro) was : 1). Enhance the role and performance of formal institutions, 2). Enhance and expand partnerships between government, private sector, non-governmental organizations and the public, 3). Develop in-situ conservation as a major conservation program, 4). Diversification and intensification of efforts to support conservation of coconut crab, 5). Improve the implementation and regulations to support the success of the coconut crab conservation.